PERAN PEMERINTAH DAERAH DALAM MEMBINA PACU JALUR TAHUN 2022-2023 - Luthfi, Azhar; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
One of the tourism in Kuantan Singingi Regency that is still preserved and maintained to this day is the pacu Jalur culture. The Department of Culture and Tourism is an element that implements government affairs that are the authority of the region in the field of culture and tourism according to Regent Regulation Number 8 of 2022. Government service efforts in developing tourism are essentially efforts to utilize objects. This study raises the theme of pacu Jalur culture because it is interested in what development will be carried out by the local government to increase the extensibility of pacuan athletes in Kuantan Singingi. This study aims to find out what developments the Kuantan Singingi Regency government has provided to foster the pacu Jalur culture and the stages of development carried out by the Kuantan Singingi Regency government to foster Jalur. The research method used is a qualitative method. This type of research is descriptive research. The location of the research is at the Tourism Office of Kuantan Singingi Regency. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. This study found that the Kuantan Singingi Regency Government, Riau Province, has several special programs to maintain and preserve the Pacu Jalur culture. The development and development of Pacu Jalur in Kuantan Singingi Regency involves the active role of the village, sub-district, and regency governments, which are supported by the Village Budget to budget funds for youth and sports development and community mutual cooperation. The government provides permits and facilities for the creation of tracks and athlete training, and promotes the Pacu Jalur culture through various events and media. In addition, the regency, provincial, and national governments support with APBD and APBN funds, build training centers, give awards to outstanding athletes, and invite international participants to participate. Keywords : Department of Culture and Tourism, Kuantan Singingi Regency, Pacu Jalur, Coaching.